The structure of cervical diseases in women suffering from pelvic floor dysfunction - Mekan R. Orazov; Liliia R. Toktar; Gulirano A. Karimova; Dmitrii G. Aryutin; O'Tosin M. Apata; Irina A. Mullina (IP Berlin A.V., 2021)
Background. The prevalence of pelvic floor dysfunction (PFD) is soaring steadily. The protrusion of the cervix beyond vaginal opening when exposed to environmental factors can lead to the development of dystrophic, sclerotic and neoplastic processes of the cervix, which are mediated by changes in the pH, biocenosis of the vagina and environmental factors. Aim. To study the pathogenesis of cervical diseases in patients with PFD. Materials and methods. The study design is an open-label prospective observational study. The study included 40 patients of reproductive age: 26 patients with cervical disease with PFD (PFD group), 14 patients without cervical disease and PFD made up the second group. Results. The patients included in the study were comparable in terms of age and body mass index. Pap smear analysis revealed that the average number of leukocytes is significantly higher in patients with PFD compared to patients in the group without PFD 5.5 (1.520.0) and 1.5 (1.56.5) respectively (p=0.040). In PFD group, a high prevalence of the following conditions was observed: cervical leukoplakia (15%), CIN1 (38.5%), CIN2 (8%), chronic cervicitis (38.5%). Onco-cytological test results reviewed where the high prevalence of parakeratosis and hyperkeratosis (15%), ASCUS (15%), LSIL (23%) and HSIL (8%) were also noteworthy. It was observed that human papillomavirus type 16 was predominant in PFD patient group. Conclusion. The data obtained indicates an increased risk of developing cervical diseases in patients with PFD.